Prevalence and clinical characterization of HPV-induced oropharyngeal cancers: the experience of the Portuguese Oncological Institute in Porto - Fernandes, Ana Teresa Perdigão Vaz (2023)
Introduction: Head and neck squamous cell carcinoma (HNSCC) represents the eighth most common cancer worldwide. Alongside traditional risk factors such as smoking and excessive alcohol consumption, HPV is now recognized as the etiologic factor driving carcinogenesis for HNSCCs of the oropharynx. Recently, multiple investigational groups have found that in the last two decades there has been a rising incidence of oropharyngeal squamous cell carcinoma (OPSCC) with a decrease in the incidence of other head and neck cancers, likely due to declines in alcohol and tobacco abuse. There is robust evidence in the literature supporting the etiologic role of HPV in a subset of OPSCC that have a distinct epidemiologic profile, and also, a strong evidence to show that HPV positive status is an independent marker of favorable prognosis for OPSCC, with an improved response to treatment and survival. Objectives: To review the current scientific evidence about the new entity of head and neck cancer: human papillomavirus positive (HPV+) oropharyngeal squamous cell carcinoma (OPSCC) and to retrospectively analyze the set of patients diagnosed in the period between 2018 till 2021 with OPSCC in Portuguese Oncological Institute Porto (IPO-Porto), in order to determine the prevalence of HPV+ OPCSS and to make a clinical characterization of patients with oropharyngeal cancers. Methods: A bibliographic search and a review of the scientific literature about the topic were carried out using the PubMed, ClinicalKey, Jama, NCCN and other scientific platforms. Regarding the IPO study, the medical records of each patient were analyzed, and p16 status, age, gender, TNM-stage, treatment and survival were recorded. Statistical analysis was performed. Results: In total, 280 patients were included. Immunohistochemically (IHC), p16 protein overexpression was only present in 57 (20.4%) of the 280 cases. The vast majority of patients (223, 79.6%) were HPV negative. According to the gender the patients were mostly male (254, 90.7%). 80 (28.6%) patients had low-T-stage (T1/T2) OPSCC tumors, and the others 197 (70.4%) had high-T-stage (T3/T4) OPSCC tumors. 74.5% of the stage I/II tumors were HPV +, and only 25.5% were HPV-. Regarding patients with advanced stages III/IV, only 7.1% were HPV+ and 92.9% were HPV-. 3 (1.1%) cases were T0. 226 (80.7%) patients showed clinically positive lymph node metastasis (cN+). According to the 8th UICC/AJCC TNM classification, 55 (19.6 %) patients were at a low clinical stage (I/II). The overall 2-years survival rate was 63.5%. The 2-years survival rate in stage I-II was 89.2% and 57.2 % in stage III-IV. The HPV+ group had a better prognosis than the HPV- group (OS: p = 0.014, DFS: p = 0.45). Discussion: There are few reports about HPV-related cancers prevalence in Portugal. One of the strengths of this study was the evaluation of HPV status using p16 immunohistochemistry (IHC) for HPV detection. p16 protein overexpression is a surrogate marker for HPV-related oropharyngeal carcinoma and has been researched in all patients (n=280). In contrast to most European countries and the USA, only a minority of patients (20.4%) in the sample were p16 positive. It may reflect differences in sexual behaviors (type of sex, age at onset of sex, number of sexual partners) of the Portuguese population for 6-7 decades ago “less liberal” compared to other Western societies. The HPV+ group had a significantly better prognosis than de HPV – group in terms of overall survival (OS) and disease- free survival (DFS), and this is in line with the published studies. This study has some limitations, the retrospective analysis might have hampered the accurate characterization of some patient risk factors, such as tobacco and alcohol use and there is a chance that p16 could have been inactivated by mutation or promoter methylation. This may be one of the possible explanations for the low rate of p16+ in our sample. Conclusion: The prevalence of HPV-related cancers in IPO-Porto is low, when compared to other studies focused on developed countries. Accordingly to literature review, the HPV-related OPSCC had a significantly better prognosis than de non-HPV – related group in terms of overall survival (OS) and diseasefree survival (DFS).